Perspective of Employment Relations and Wages in Labor Law and Islamic Law - Kunarti, Siti; Handayani, Sri Wahyu; Ardhanariswari, Riris; Faisal, Faisal (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
The implementation of work employment and wages is not in line between labor and Islamic law. This study aimed to review and analyze labor employment and wage arrangements from perspectives on labor law and Islamic law. This research used a normative juridical method with a contextual approach, rules and regulations, the Quran, and hadith. The results showed that Islamic and labor laws have the same goal: that workers can live decent lives. In labor law, work relations are born from work agreements, and wages are the right of workers after obligations are carried out. However, in Islamic law, work relations are based on justice without exploitation, are efficient, and do not violate other sharia principles, and wages are included in the study of Ijarah. The concept of employment is based on time, type of work, and targets obtained. F or work relations and wages to fulfill human dignity, it is necessary to contain labor regulations that pay attention to the principles of relations and wages in Islamic law.